Development of Real-Time Reporting Features in A Quality Audit Information System For Higher - Achmad Naufal Amirul Hidayat Amir; Agus Sifaunajah (KH. A. Wahab Hasbullah University, 2026)
This study presents the development of a real-time reporting feature within an Internal Quality Audit Information System to support more effective monitoring and evaluation processes in higher education institutions. The system was enhanced to address common limitations found in conventional audit mechanisms, particularly delays in reporting, difficulties in tracking audit progress, and inconsistencies in presenting the most recent audit data. The real-time reporting component was developed using AJAX polling integrated with CodeIgniter 4, enabling automatic updates of audit indicators without requiring page reloads. The system architecture incorporates a relational MySQL database, modular controllers, and an interactive dashboard interface for presenting audit achievements, completeness percentages, and detailed indicators for both faculties and study programs. The solution achieves an average data synchronization latency of 2.4 seconds, a 100% success rate in functional black-box testing, and a System Usability Scale (SUS) score of 82.5 (Excellent category) among internal auditors, demonstrating high acceptability and significantly enhancing the responsiveness of decision-makers during the audit cycle.